(untitled) (Journal of the College of Basic Education, 2023)
There is no direct definition of this term separately which helps to derive a definition of grammatical concepts by presenting the ’concept’.Al-Mufhum: Language: It came in Lisan Al-Arab: “Understanding: Your knowledge of something with the heart, and understanding of it with understanding and understanding, and Fahama: His knowledge, the last one from Sibawayh, and I understood the thing I reasoned and knew it, and I understood so-and-so, I understood it, and understanding of speech: He understood it bit by bit, and a man of understanding is quick to understand, It is said: He understood, and he understood, and the matter made him understand it, and he made him understand it: he made him understand it, and he asked him to understand it: he asked to be understood. The thing asked me to understand, so I understood it in an understanding manner.Al-Mufhum: Language: It came in Lisan Al-Arab: “Understanding: Your knowledge of something with the heart, and understanding of it with understanding and understanding, and Fahama: His knowledge, the last one from Sibawayh, and I understood the thing I reasoned and knew it, and I understood so-and-so, I understood it, and understanding of speech: He understood it bit by bit, and a man of understanding is quick to understand, It is said: He understood and he understood. And the matter made him understand and he made him understand it: He made him understand it, and he asked him to understand it: He asked to be understood. The thing asked me to understand, so I understood it in an understanding way” (Ibn Manzoor, 2005, vol. 11: 235).Idiom: Everyone knew himNader and others: that it is “a mental perception that results from realizing the relationships and common elements between a group of phenomena, events, or things, for the purpose of classifying them into categories that are fewer in number than them.”(Nader et al., 15:2000).Shehata: That it is “a mental formation that arises from the abstraction of a characteristic or more from partial cases, multiple examples, with the availability of each of this property, where the property is isolated from what surrounds it.Al-Taiti: that it is “a verbal symbol indicating specific information and ideas for things or experiences that have common qualities or characteristics.” (Al-Taiti, 69: 2007).Operational definition:It is a term expressed by symbols, words, names, or a number of common characteristics that represent a link between a group of facts and events for the purpose of reducing them to one category and knowing the relationships between them.GrammarLanguage: It came in the dictionary of standards of language: “Nun, Ha, and Waw are words that indicate intention, and that is why it is called towards speech, because it means the origins of speech, so it speaks according to what the Arabs used to speak.”(Ibn Faris, 1972, vol. 5: 403).